Effect of Nedocromil Sodium on Polymorphonuclear Leukocyte Plasma Membrane - A. Kantar; N. Oggiano; P. L. Giorgi; G. V. Coppa; R. Gabbianelli; S. Bruni; F. M. Cutrona; R. Fiorini (Hindawi Limited, 1994)
The effect of nedocromil sodium on the plasma membrane fluidity of polymorphonuclear leukocytes (PMNs) was investigated by measuring steady-state fluorescence anisotropy of 1-[4-trimethylammonium-phenyl]-6-phenyl- 1,3,5-hexatriene (TMA-DPH) incorporated in the membrane. Our results show that nedocromil sodium 300 μM significantly decreased membrane fluidity of PMNs. The decrease in membrane fluidity of PMNs induced by fMLP was abolished in the presence of nedocromil sodium. These data suggest that nedocromil sodium interferes with the plasma membranes of PMNs and modulates their activities.